Wuwei Qingzhuo San Ameliorates Hyperlipidemia in Mice Fed With HFD by Regulating Metabolomics and Intestinal Flora Composition - Ge, Shasha; Liao, Cuiping; Su, Duna; Mula, Tunuo; Gegen, Zhula; Li, Zhiyong; Tu, Ya (Frontiers in Pharmacology, 2022)
Hyperlipidemia is one of the most common metabolic disorders that threaten people’s health. Wuwei Qingzhuo San (WQS) is a traditional Mongolian medicine prescription, which is widely used in Mongolia for the treatment of hyperlipidemia. Our previous found that it has hypolipidemic and hepatoprotective effects on hyperlipidemic hamsters. However, the underlying lipid-lowering mechanisms of WQS and its relationship with intestinal flora is not yet clear. In the present study, 16S rRNA gene sequencing and metabolomics were performed to investigate the action mechanism of WQS on hyperlipidemic mice induced by high-fat diet (HFD). As a result, metabolic pathway enrichment analysis revealed that the intervention of WQS had obvious modulated the metabolism of α-linolenic acid and linoleic acid metabolism and the biosynthesis of bile acid. 16S rRNA sequencing showed that WQS had altered the composition of the intestinal microbiota in hyperlipidemic mice fed with HFD, especially adjusted the relative abundance ratio of Firmicutes/Bacteroides. These findings provide new evidence that WQS can improve HFD-induced hyperlipidemia by regulating metabolic disorders and intestinal flora imbalance.